Assessing bioactivity-exposure profiles of fruit and vegetable extracts in the BioMAP profiling system. (February 2019) - Wetmore, Barbara A.; Clewell, Rebecca A.; Cholewa, Brian; Parks, Bethany; Pendse, Salil N.; Black, Michael B.; Mansouri, Kamel; Haider, Saad; Berg, Ellen L.; Judson, Richard S.; Houck, Keith A.; Martin, Matthew; et al.
Abstract: The ToxCast program has generated in vitro screening data on over a thousand chemicals to assess potential disruption of important biological processes and assist in hazard identification and chemical testing prioritization. Few results have been reported for complex mixtures. To extend these ToxCast efforts to mixtures, we tested extracts from 30 organically grown fruits and vegetables in concentration-response in the BioMAP® assays. BioMAP systems use human primary cells primed with endogenous pathway activators to identify phenotypic perturbations related to proliferation, inflammation, immunomodulation, and tissue remodeling. Clustering of bioactivity profiles revealed separation of these produce extracts and ToxCast chemicals. Produce extracts elicited 87 assay endpoint responses per item compared to 20 per item for ToxCast chemicals. On a molar basis, the produce extracts were 10 to 50-fold less potent and when constrained to the maximum testing concentration of the ToxCast chemicals, the produce extracts did not show activity in as many assay endpoints. Using intake adjusted measures of dose, the bioactivity potential was higher for produce extracts than for agrichemicals, as expected based on the comparatively small amounts of agrichemical residues present on conventionally grown produce. The evaluation of BioMAP readouts and the dose responses for produce extracts showed qualitative and quantitative differences from results with single chemicals, highlighting challenges in the interpretation of bioactivity data and dose-response from complex mixtures. Highlights: Bioactivity of mixtures extracted from 30 organic produce samples was assessed using the BioMAP panel Produce samples were 10 to 50-fold less potent than ToxCast compounds on an estimated molar basis. Constraining to maximum testing concentration of ToxCast chemicals, the produce samples displayed less activity. A relative intake dose metric is proposed to integrate differences in potency. A framework highlighting approaches for risk-based decision making for mixtures is outlined.